Implementasi Math Clinic Dalam Meningkatkan Kemampuan Matematis Siswa Dengan System Pembelajaran Hibryd - Nainggolan, Arisan Candra; Sitepu, Israil (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
The sudden appearance of Covid-19, which has disrupted the stability of almost all lines of life on earth, has now begun to subside. The learning and teaching process in schools has also entered the new normal, even face-to-face learning has been 100% enforced. However, the war between Russia and Ukraine which is still going on today has had a negative impact on the global economy. Globally, the war in Ukraine is a